Chunky Bag Craft Development for PKK Group Empowerment Based on the ABCD Approach - Rianti, Titis Surya Maha (SMONAGENES Research Center, Univeritas Brawijaya, 2025)
Developing creative skills for the Family Welfare Movement (PKK) is one way to open business opportunities and increase household income. The purpose of this activity is to enhance the PKK group’s knowledge and skills and cultivate a desire to establish a Chunky Bag craft business. Community Service was carried out with the PKK group in Tlogomas Village, involving 16 participants. The activity was carried out using the Asset-Based Community Development approach through three main stages: preparation, implementation of the training program, and evaluation. The training was carried out through several sessions: an introduction to basic knitting techniques; an introduction to chunky bags; practice making chunky bags; and managing a small chunky bag business and its sales prospects. The activity was implemented successfully with high participant enthusiasm, exceeding the target by 106.67%. Prior to the training, most participants (68.75%) had no prior knitting experience, while 62.5% reported high familiarity with basic knitting techniques after the training. All participants successfully made chunky bags during the training, were satisfied with the results, and expressed interest in making and selling them, either individually or in groups. Thus, chunky bag craft training has a significant impact on the targets, including increased knowledge, enhanced skills, and a desire to become entrepreneurs.